Analisis Strategi Pemasaran Pengusaha Batik Kelurahan Banyurip Pekalongan Dengan Pendekatan Marketing Mix Berbasis Syariah - Arwani, Agus (Institut Agama Islam Negeri Kendari, 2019)
This study aims to explore the marketing strategies of Banyurip urban batik entrepreneurs in Pekalongan city, with qualitative types of filed research. The collection technique uses interview, observation and documentation methods. The results of the study that batik entrepreneurs in Banyurip village had carried out marketing mix marketing strategies, they made various batik products, with cash and tempo prices, distribution by coming to the market, batik shops, shipping packages, and through Loper and resellers, market coverage from the city, outside the city to outside Java and even abroad, most of them use direct selling promotions, and utilize social media technology. Batik entrepreneurs in general as much as 75% have applied the principles of sharia marketing mix. The 25% have not perfectly implemented sharia principles with those who still use the services of interest-based financial institutions for production capital, in addition there are still entrepreneurs who dispose of batik waste water directly. The strength possessed by entrepreneurs produce batik products with various types, motivations and patterns, the weakness is capital and less competent workforce, the opportunity is to maximize technology and maintain trust, while the threat is raw materials which tend to rise but selling prices lower and more competition.